The influence of parenting on building character in adolescents - Rini Sugiarti; Erwin Erlangga; Fendy Suhariadi; Mulya Virgonita I. Winta; Agung S. Pribadi (Heliyon, 2022)
Character building in adolescents starts from childhood and continues throughout the life span. Character building in adolescents is associated with psychosocial development and is very important because it will be a strong foundation for their personality. The purpose of this study was to empirically test the influence of parenting on character building in adolescents. As many as 415 adolescents were involved in the study. The sampling technique used is Cluster Random Sampling. Tools used in this study are in the form of two scales, namely Character Building Scale and Parenting Scale. The scale of youth character building includes three indicators: peace, respect for difference, and awareness. The parenting scale consists of three indicators: parental cooperation, child tolerance, and warmth. Date are analyzed using Simple Regression Analysis. This study showed that, although less significant, parenting influences character building in adolescents. Understanding that the impact of parenting on character formation in adolescents is less critical, in character formation in adolescents it is therefore necessary to pay attention to other factors, namely schools and communities. This study also provides a strengthening understanding that adolescents with cheerful character receive positive social support from their social environment.